Decentralization, Local Powers and Social Participation in Education in Bolivia: The Cases of Tarabuco and La Paz (1997-2003) - Yapu, Mario (Education Policy Analysis Archives, 2007)
Since the Declaration of ministers of education of iberoamerican countries held in Santa Fe de Bogotá, November 4-6, 1992, the decentralization of education has been a recurrent subject of educational reforms in Latin American countries, where in some of them the experiences of decentralization have preceded said Declaration while in others they have followed it. The educational reforms that have come about within the last years associate the decentralization of education with social participation and improvements in the quality of education, among other subjects. This article discusses these topics, questioning what type of decentralization would be effective in Bolivia, which would be the characteristics of social participation and how it is affecting the quality of education. The analysis is done using a micropolitical approach and its emphasis is on the social practices of the actors (i.e., local authorities, teachers and parents), grounding its methodology in two case studies: La Paz and Tarabuco (Bolivia). It is suggested that policies of education decentralization and theoretical social sciences approaches have not been successful in explaining the phenomenon of social relations of power at the local level that affects the nature of any decentralization process, because at the core of State power there is a hegemonic dominance of the managerial approach and a vision of education that is essentially bureaucratic.